Employment protection: the case of limited enforceability - Florian Baumann (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper shows that the effects of employment protection critically depend on its enforcement. For this purpose, we capture evasion of employment protection via market exit in a setting of monopolistic competition. We find that the number of firms entering the market depends on firing costs only in the case of imperfect enforcement of employment protection. Furthermore, the possibility to circumvent firing restrictions by exiting the market mitigates the adverse efficiency effects of employment protection and can reverse the sign of the change in employment associated with an increase in firing costs.
Keywords: J63; J65; L13; 330; Employment protection; evasion; market entry and exit; Kündigungsschutz; Rechtsdurchsetzung; Markteintritt; Monopolistischer Wettbewerb; Beschäftigungseffekt; Theorie